If
lim x → 1 x − 1 3 x − 1 = b a ,
evaluate a + b .
NOTE:
No L'Hôpital's Rule.
Problem credit: Calculus: 6E, James Stewart
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A simpler approach would be to make the substitution y = x and then use the identity y → a lim ( y − a y n − a n ) = n a n − 1
perfect answer
Why no L'Hopital's rule? ⌢ ¨
L'Hopital's rule gives x → 1 lim 3 3 x 2 2 x = 3 2 so our answer is 5 .
I know right, L'Hopital makes this problem a one-liner :D.
Log in to reply
Exactly. That's why we don't use it. The point is to demonstrate your algebraic skills.
Problem Loading...
Note Loading...
Set Loading...
Let u = 6 x . Then u → 1 as x → 1 , and the limit then becomes
lim u → 1 u 3 − 1 u 2 − 1 = lim u → 1 ( u − 1 ) ( u 2 + u + 1 ) ( u − 1 ) ( u + 1 ) = lim u → 1 u 2 + u + 1 u + 1 = 3 2 .
Thus a = 2 , b = 3 and a + b = 5 .